2015
DOI: 10.1016/j.jphotobiol.2015.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of manganese species in an oxidative dimerization reaction of a bis-terpyridine mononuclear manganese (II) complex and their heterogeneous water oxidation activities

Abstract: Heterogeneous water oxidation catalyses were studied as a synthetic model of oxygen evolving complex (OEC) in photosynthesis using mica adsorbing various manganese species. Distribution of manganese species formed in the oxidative dimerization reaction of [Mn(II)(terpy)2](2+) (terpy=2,2':6',2″-terpyridine) (1') with various oxidants in water was revealed. 1' was stoichiometrically oxidized to form di-μ-oxo dinuclear manganese complex, [(OH2)(terpy)Mn(III)(μ-O)2Mn(IV)(terpy)(OH2)](3+) (1) by KMnO4 as an oxidant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Yagi suggested that the real active species converted from manganese complex on clay is manganese cluster-based catalyst rather than manganese oxide [81,88]. Thus, the transformation of 15 is still unclear.…”
Section: Molecular Manganese Complexes As Precursorsmentioning
confidence: 99%
“…Yagi suggested that the real active species converted from manganese complex on clay is manganese cluster-based catalyst rather than manganese oxide [81,88]. Thus, the transformation of 15 is still unclear.…”
Section: Molecular Manganese Complexes As Precursorsmentioning
confidence: 99%
“…In recent years, low-cost 3d metals have enjoyed tremendous interest among the scientific community for their cost and abundance. Recently, several complexes of 3d metal, e.g., manganese, iron, cobalt, and nickel have been studied. Copper is the latest member of this league.…”
Section: Introductionmentioning
confidence: 99%